My experience as an exchange student at Linköping - Shrestha, S (Kathmandu University Medical Journal, 2010)
DOI: 10.3126/kumj.v7i2.2719 Kathmandu University Medical Journal (2009) Vol.7, No.2 Issue 26, 185-187